RSR1, a ras-like gene homologous to Krev-1 (smg21A/rap1A): role in the development of cell polarity and interactions with the Ras pathway in Saccharomyces cerevisiae. - Ruggieri, R (1992)
The Saccharomyces cerevisiae ras-like gene RSR1 is particularly closely related to the mammalian gene Krev-1 (also known as smg21A and rap1A). RSR1 was originally isolated as a multicopy suppressor of a cdc24 mutation, which causes an inability to bud or establish cell polarity. Deletion of RSR1 itself does not affect growth but causes a randomization of bud position. We have now constructed mutant alleles of RSR1 encoding proteins with substitutions of Val for Gly at position 12 (analogous to constitutively activated Ras proteins) or Asn for Lys at position 16 (analogous to a dominant-negative Ras protein). rsr1Val-12 could not restore a normal budding pattern to an rsr1 deletion strain but could suppress a cdc24 mutation when overexpressed. rsr1Asn-16 could randomize the budding pattern of a wild-type strain even in low copy number but was not lethal even in high copy number. These and other results suggest that Rsr1p functions only in bud site selection and not in subsequent events of polarity establishment and bud formation, that this function involves a cycling between GTP-bound and GDP-bound forms of the protein, and that the suppression of cdc24 involves direct interaction between Rsr1p[GTP] and Cdc24p. Functional homology between Rsr1p and Krev-1 p21 was suggested by the observations that expression of the latter protein in yeast cells could both suppress a cdc24 mutation and randomize the budding pattern of wild-type cells. As Krev-1 overexpression can suppress ras-induced transformation of mammalian cells, we looked for effects of RSR1 on the S. cerevisiae Ras pathway. Although no suppression of the activated RAS2Val-19 allele was observed, overexpression of rsr1Val-12 suppressed the lethality of strains lacking RAS gene function, apparently through a direct activation of adenyl cyclase. This interaction of Rsr1p with the effector of Ras in S. cerevisiae suggests that Krev-1 may revert ras-induced transformation of mammalian cells by affecting the interaction of ras p21 with its effector.